How an intake conversation in mental healthcare nearly led to suicide - Lies Sercu (The Beryl Institute, 2022)
As a patient of mental health care, I want to share and reflect on an experience I had during an intake conversation. I had been dismissed from a hospital stay and my psychiatrist had arranged for an intake conversation for a program specialized in treating people with anxiety and depression in another hospital. Given the state of my illness, I was prepared to give this new program a try. My expectations were that I would be treated with dignity and respect as I had been treated in the hospital from which I had been dismissed. Yet, my experience turned out to be very negative leading me to consider suicide right after the conversation and when getting home. Below, I first provide my narrative of the intake conversation, after which I will share some reflections and recommendations. I now understand that achieving patient-centered care during intake conversations is not obvious, in part because the intaker has little time to get to know the patient, and in part because the patient may defer from speaking openly with the intaker. My conclusion is that, if the intaker and the patient manage to negotiate and work together from different but complementary points of view, one can achieve a patient-centered partnership in care, already during intake conversations. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.